Linking Non-renewable and Renewable Electricity and Government Expenditures to Environmental Degradation: Evidence of 10 Newly Industrialized Countries - Bouchoucha, Najeh; Ghandri, Mohamed; Yahyaoui, Ismahen (International Journal of Energy Economics and Policy, 2024)
This research aims to identify the relationship between non-renewable electricity (NRE), renewable electricity (RE) and government expenditures (EXPD) on environmental degradation using the ARDL model for 10 Newly Industrialized Countries (NIC) during the period 1990-2021. Our empirical findings show that the NRE increases the CO2 emissions, however the RE decrease the CO2 emissions in the long and short run. For the effect of governement expenditure on the environment, it may be classified as direct and indirect. In fact, EXPD affect positively the CO2 emissions. In contrast, The indirect effect operates through the interaction between EXPD and NRE and RE. Our results demonstrate that the interaction between EXPD and NRE affects negatively the CO2 emissions. Nevertheless, the impact of the interaction between EXPD and RE on the CO2 emissions is more important. The results show also there is a bidirectional causality between each variable and CO2 emissions. With the empirical findings as a basis, we suggest that the NI countries should reduce NRE consumption and enhance the environmental expenditures so that they may produce more RE to combat environmental issues.